Seismotectonics of the frontal Himalaya through the electrical conductivity imaging - Arora, B.R. (My University, 2002)
The geomagnetic induction response functions as deduced from the number of geomagnetic deep sounding experiments in the frontal Himalaya and contiguous Indian shield have been used to map geoelectrical structures of the Frontal Himalaya. The anomalous induction features have shown presence of an elongated conductive structure embedded in high seismicity zone emerging out of the Himalaya. The nature of electrical conductivity distribution along a profile extending from the Indian shield to higher Himalaya shows evidence of a mid-crustal conductor beneath the Indo-Gangetic Plains. This conducting layer dips down at the Main Frontal Thrust and underthrusts the Himalaya as low-angle dipping plane. Beneath the frontal Himalaya, top surface of the mid-crustal conductor correlates with a plane defined by hypocenters of moderate earthquakes. It also defines the cut-off depth of crustal micro-seismicity. It is suggested that conducting zone represents a thermal/metamorphic boundary below which fluids, driven off from the down-going sediments or produced by the dehydration reactions, are trapped. While the presence of fluids can account for the high conductivity, the fluid saturated slab at mid-crustal depth tends to simulate onset of ductile behaviour and hence defines the cut-off depth of the crustal seismicity. Presence of fluids along the thrust planes or detachment plane can reduce the sliding resistance and, hence, focus tectonic deformations along a linear plane, as evidenced by the alignment of the foci of moderate earthquakes. Consideration of the space-time pattern in seismicity, in relation with the high conductivity zone, permits to infer that the nature of electrical conductivity distribution could be a sensitive pointer of the reactivation of the sub-surface structures that lead to earthquakes.
Keywords: Seismotectonics; Electrical conductivity imaging; Geomagnetic deep sounding; Himalaya; Earthquake